2018
DOI: 10.29252/jcbr.2.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of One Session of Resistance Training with and without Blood Flow Restriction on Serum Levels of Creatine Kinase and Lactate Dehydrogenase in Female Athletes

Abstract: Introduction: Intense exercise may cause immunological changes and muscle damage. The aim of this study was to investigate the effect of one session of resistance training with and without blood flow restriction on serum levels of creatine kinase (CK) and lactate dehydrogenase (LDH) in female athletes. Materials and Methods: In this semiexperimental study, 30 female basketball players were randomly divided into a traditional resistance training group (without blood flow restriction), a resistance training grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(14 reference statements)
2
2
0
1
Order By: Relevance
“…These markers displayed a similar increase after the preseason period for both teams, and confirmed an aftereffect muscle damage in the participants [55]. This finding comes in agreement with the study of Khajehlandi and Janbozorgi [41], that demonstrated a similar increase in CK and LDH enzymes in female basketball athletes after only a single session of exercise. Finally, no significant correlations were found between the examined markers and the position (center, forward, guard) or the basic characteristics (age, height, weight) among athletes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These markers displayed a similar increase after the preseason period for both teams, and confirmed an aftereffect muscle damage in the participants [55]. This finding comes in agreement with the study of Khajehlandi and Janbozorgi [41], that demonstrated a similar increase in CK and LDH enzymes in female basketball athletes after only a single session of exercise. Finally, no significant correlations were found between the examined markers and the position (center, forward, guard) or the basic characteristics (age, height, weight) among athletes.…”
Section: Discussionsupporting
confidence: 90%
“…Increased muscle mass and elevated levels of testosterone have been previously correlated with elevated CK levels [24,38], which may explain why male athletes appeared to have higher CK and LDH activities compared to females [39]. Also, CK and LDH levels were significantly higher after the preseason period for both of the teams, a finding that comes in agreement with previous studies that demonstrated a significant increase in CK and LDH levels after 2 h of high-intensity basketball training (208.41%), or after a single resistance training unit (6-12%) [40,41]. Significant increases have been also observed after an official basketball match (~125-160%) [16,42], or during a competitive basketball season [43,44].…”
Section: Discussionsupporting
confidence: 88%
“…Hormonal analyses revealed significant GH and normetanephrine differences pre- and post-exergame in both groups, though no between-group differences emerged for GH or normetanephrine, with BFR groups showing minor increases. Exercise enhances sympathetic nervous system activity, upregulating catecholamine release, and thus stimulating GH secretion [ 15 ]. Increases in GH levels after a low-intensity training session with BFR have been shown to elevate threefold over the baseline in a cohort of college-aged females [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using short-term Fourier transform time-frequency analysis, recent investigations have shown that HRV decreases following moderate to high-intensity exercise [14]. In addition, recent data suggest that peak lactate accumulation is higher immediately post-exercise under BFR conditions [15]. Considering the anabolic effects of lactate, it is possible to improve muscle hypertrophy using BFR compared with exercise alone [16].…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, os resultados da inferência baseada na magnitude, análise mais sensível que os modelos estatísticos matemáticos convencionais, e capaz de aplicar maior efeito prático/clínico [31,32] apontam que há muito provavelmente maior eficácia no GRF. Esses resultados corroboram outros estudos, que compararam magnitude de demanda fisiológica a partir das concentrações de La-em exercícios com e sem restrição de fluxo sanguíneo [33,34]. Achados estes que vão de encontro aos de Yasuda et al [35], que observaram vantagem para treinamento de alta intensidade para obter maior demanda metabólica.…”
Section: Discussionunclassified